The Role and Conditions of Information Flow in the Management of Supply Chains in Enterprises Operating in the Metal Industry - Ewa STANIEWSKA (Communications of International Proceedings, 2021)
This study presents the results of research on the role and conditions of information flow in the context of relation development and supply chain management in metal industry enterprises. The research was conducted using a proprietary questionnaire and covered businesses operating in Poland. The examined issues included elements such as: assessing the impact of improvements to information flow and implementation of modern IT systems, identifying the scope of information exchange, tools used and actions taken to increase the effectiveness of tasks carried out in the area of information flow and integration, issues of information transfer, confidentiality and their role in building trust in the supply chain, assessing the risk and barriers occurring in relations with business partners in the supply chain.
Keywords: Supply Chain Management; Information Flow; Information Security; Metal Industry